2005
DOI: 10.1007/s00774-004-0553-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of serum 25-hydroxyvitamin D and intact parathyroid hormone levels in a normal Japanese population

Abstract: We conducted an observational study in order to assess the prevalence of hypovitaminosis D and its seasonal changes, in the Tokai area (N35.3 E137.0), in 197 normal subjects in Japan. The mean serum 25-hydroxyvitamin D (25-OHD) level measured by direct radioimmunoassay (RIA) was lowest at the end of winter, and highest at the end of summer (15.1+/-7.1 ng/ml in March; 21.5+/-5.5 ng/ml in June; 31.6+/-5.6 ng/ml in September; 23.1+/-5.3 ng/ml in December; mean+/-SD). The prevalence of hypovitaminosis D (<20 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 23 publications
7
57
1
2
Order By: Relevance
“…1). As in previous studies on normal population [3,12,17], serum intact PTH levels were negatively correlated with serum 25-OHD concentrations in our populations (Fig. 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1). As in previous studies on normal population [3,12,17], serum intact PTH levels were negatively correlated with serum 25-OHD concentrations in our populations (Fig. 2).…”
Section: Resultssupporting
confidence: 88%
“…These findings suggest the decreased bioavailability of vitamin D3 due to its deposition in body fat component in obese population. In Japanese nonobese population, we have previously reported that not body fat content but BMI was positively associated with the increase of serum concentration of 25-OHD, suggesting the increase of the amount of non-fat tissue components such as skeletal muscles is related to the increase of 25-OHD [17]. As changes in body weight and body fat distribution are known to be closely related to insulin resistance and the occurrence of type 2 diabetes [26], these results suggest that the imbalance of body composition, for example the increase of visceral fat, in diabetes patients may contribute to the relationship between serum 25-OHD concentration and BMI.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, the vitamin D status in Japan is relatively better in the regions in South Asia and positively related to fish consumption [49][50][51]. Prevalence of hypovitaminosis D (<30 nmol/L) in women over 30 years old is only 10.3% [49] and in active elderly (25(OH)D <75 nmol/L) is below 5% [50].…”
Section: Asiamentioning
confidence: 99%
“…Similarly, Kashi et al 16 showed that both genders had 25-(OH)D deficiency in the summer and winter. On the other hand, a study by Ono et al 17 showed that the serum 25-(OH)D levels were higher in men than in women, but these differences could be related to how much skin was covered as well as their jobs.…”
Section: Discussionmentioning
confidence: 93%